Management and Outcomes of Severe Submergence in Second Premolar: Penanganan dan Hasil dari Submergensi Parah pada Premolar Kedua - Wanda Karisma Dian Sari; Windy Yuliartanti; Eka Setyawardana (Academia Open, 2024)
General Background: The early loss of primary molars is a prevalent dental issue that can lead to significant occlusal disturbances, including space reduction and misalignment of permanent teeth. Specific Background: Submergence of the second permanent molar following premature exfoliation of primary molars exacerbates these issues, complicating the eruption pattern and dental arch integrity. Knowledge Gap: Despite existing treatment modalities, there is limited evidence on the effectiveness of specific appliances in managing severe submergence cases in pediatric patients. Aims: This study aims to evaluate the efficacy of the Gerber Space Regainer in restoring lost space and correcting the alignment of submerged second premolars in a pediatric patient. Results: A 10-year-old patient experiencing significant space loss due to premature exfoliation of tooth 85 was treated with a Gerber Space Regainer. Over a 7-week period, the appliance successfully regained 8 mm of space, with notable uprighting of the affected premolar, achieving complete recovery of the dental arch. Novelty: This case report highlights the practical application and success of the Gerber Space Regainer, emphasizing its efficiency in a short time frame, which has not been extensively documented in similar clinical scenarios. Implications: The findings suggest that the Gerber Space Regainer is an effective and reliable option for managing complex orthodontic cases involving submergence and space loss, contributing to the enhancement of treatment protocols in pediatric dentistry. Highlights: Effective space recovery: The Gerber Space Regainer successfully restored 8 mm of lost dental arch space in 7 weeks. Improved alignment: The treatment led to the uprighting of the submerged second premolar, ensuring proper occlusion. Pediatric applicability: The appliance demonstrated high efficiency and compliance in a young patient, showcasing its potential in pediatric cases. Keywords: Premature Loss, Space Regainer, Submergence, Second Premolar, Eruption Disturbance